Puttaswamy: Jury still out on some privacy concerns?. Issue 2 (4th May 2017) - Kamil, Mariyam
ABSTRACT: In KS Puttaswamy v Union of India, a nine-judge bench of the Indian Supreme Court considered whether there is a fundamental right to privacy in India. The Court unanimously answered this question in the affirmative through six concurring opinions. The decision is likely to have a sweeping impact for public law in India in general, and for the right to privacy, in particular. This case note examines the implications of this decision for three specific privacy themes: the rationale for the right to privacy, standard(s) of judicial review and horizontal application. The note concludes that there is judicial convergence on the first theme, but unfortunately more questions are raised than answered in respect of the other two.